The Role of Women and Patriarchal Culture in the Field of Pre-Islamic Marriage Nawal El-Saadawi: A Historiographic Approach - Khairul Rasyidi; Muhammad Zaky Azizi (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article aims to review the role of women and patriarchal culture in matters of marriage in pre-Islamic times. This article looks at the history of women from the perspective of Nawal El Sadaawi. The approach used is a historiographic approach. Historiography is a fact-based approach to historical writing. The results obtained, First: that the role of women in the Arab Jahiliyyah period began with a matriarchal system. However, due to the superiority and will of men, the matriarchal system is gradually being eroded and replaced by a patriarchal system. Second, it shows that the power of men who want everything, especially in the field of marriage during the Arab Jahiliyyah era, made patriarchal culture even more common. Until Islamic law came, everything was covered even though there were still many things that needed to be improved. Third, historiography is a scientific approach to the study of historical facts. This shows that marriage in jahiliyyah Arabia was full of chaos.